The role of ATP1A3 gene in epilepsy: We need to know more - Zou, Shuang; Lan, Yu-Long; Gong, Yiwei; Chen, Zhong; Xu, Cenglin (Frontiers in Cellular Neuroscience, 2023)
The ATP1A3 gene which encodes the Na+/K+-ATPase α3 catalytic subunit plays a crucial role in both physiological and pathological conditions in the brain, and mutations in this gene have been associated with a wide variety of neurological diseases through impacting the whole infant development stages. Cumulative clinical evidences suggest that some severe epileptic syndromes have been linked to mutations in ATP1A3, among which, inactivating mutation of ATP1A3 has been intriguingly found to be a candidate pathogenesis for complex partial and generalized seizures, proposing ATP1A3 regulators as putative targets for the rational design of antiepileptic therapies. In this review, we introduced the physiological function of ATP1A3 and summarized the findings about ATP1A3 in epileptic conditions from both clinical and laboratory aspects at first. Then some possible mechanisms of how ATP1A3 mutations results in epilepsy are provided. We think this review timely introduce the potential contribution of ATP1A3 mutations in both the genesis and progression of epilepsy. And taken that both the detailed mechanisms and therapeutic significance of ATP1A3 for epilepsy are not yet fully illustrated, we think that both in-depth mechanisms investigations and systematic intervention experiments targeting ATP1A3 are needed, by doing so, perhaps a new light can be shed on treating ATP1A3 associated epilepsy.